The relationship between the commensal microbiota levels and Crohn's disease activity. Issue 5 (1st May 2020) - de Alencar Junior, Hagamenon; Paiotti, Ana Paula Ribeiro; de Araújo Filho, Humberto Bezerra; Oshima, Celina Tizuko Fujiyama; Miszputen, Sender Jankiel; Ambrogini‐Júnior, Orlando
Abstract: Background and aim: Human gut microbiota play an important role in metabolism and host physiology. Perturbations of the gut microbial communities lead to the development of various diseases such as inflammatory bowel disease, celiac disease, allergic diseases, and metabolic diseases. Crohn's disease is a chronic inflammatory bowel disease characterized by periods of remission and relapse. Several studies suggest that intestinal inflammation arises due to an abnormal response of the intestinal immune system to the fecal microbiota. The goal of the study was to evaluate the relative amount of four bacterial groups in fecal samples of Crohn's disease patients and their relation to the inflammatory activity. Methods: We studied stool samples of 105 individuals, 54 with Crohn's disease and 51 as a control group. The DNA extracted from the stool samples was subjected to real‐time polymerase chain reaction (qPCR) for quantification of the Bacteroidetes phylum, class Bacilli, and Bifidobacteriaceae and Enterobacteriaceae families. Results: We found a significant increase in Bacteroidetes in Crohn's disease samples when compared to the control group (14 650 and 2060 CFU/ng DNA, respectively) ( P = 0.014). On the other hand, we observed a significant reduction in Bacilli and Bifidobacteriaceae (13 and 58 CFU/ng DNA, respectively) ( P  < 0.0001). In contrast, patients without any drug treatment presented an increase of Bacilli and Bifidobacteriaceae (102 521 and 6235 CFU/ng DNA, respectively) ( P  < 0.0001). Conclusion: The commensal bacteria were decreased in fecal samples of participants with Crohn's disease when compared to the control group. There was no relation between the disease location and/or disease activity with the microbiota. Abstract : Gut microbiota is strongly associated with host physiology, and perturbations of the gut microbial communities lead to the development of various diseases. The goal of this study was to evaluate the relative amount of four bacterial groups in fecal samples of patients with Crohn's disease and their relation to the inflammatory activity. We observed that the commensal bacteria were decreased in fecal samples of participants with Crohn´s disease when compared to the control group. There was no relation between the disease localization and/or clinical condition with the microbiota.